Balık Beslemede Yeni Besin Maddelerinin Kullanımı - Keleştemur, Gülüzar Tuna; Uslu, Ali Atilla (Niyazi ÖZDEMİR, 2017)
The nutrients costs are important for aquaculture. When formulating a cost-effective diet, the cost of the ingredients as well as their nutrient content (protein, lipid, carbohydrate, essential amino acids, essential lipids, vitamins and minerals etc.) to meet the nutrient requirements in fish species, should be considered. In this study, the use of chiken egg flour instead of fish flour in fish diet as protein source was investigated in terms of nutrient quality and as economic

Costs of nutrients are important for aquaculture. When formulating a low-cost diet, the cost of ingredients(such as protein, lipids, carbohydrates, essential amino acids, essential oils, vitamins and minerals) and their nutritional content must be taken into account to meet the nutritional needs of fish species. In this study, the use of chicken egg flour instead of fish flour as a protein source in fish diets was investigated in terms of food quality and economically important.
Use of New Nutrition Materials in Fish Feeding
Keywords: Engineering; Mühendislik